From Breakdown to Breakthrough: COVID-19’s Impact on Global Governance and Lessons for Resilience - Muhammad Kamruzzaman; Md. Shofik Uddin (Asian Studies, 2025)
The COVID-19 pandemic emerged as one of the most profound global crises in modern history, exposing deep vulnerabilities in global governance structures and the interconnectedness of nations. This study explores the multifaceted causes of the crisis, the international community’s varied responses, and the critical lessons learned for strengthening resilience against future global threats. It begins by examining the origins and spread of the virus, highlighting systemic weaknesses in global health surveillance, early warning mechanisms, and the political hesitation that hampered coordinated containment efforts. A major theme of the analysis is the disparity in national responses, shaped by political systems, public health capacities, and social trust, which led to uneven outcomes across regions. The study further evaluates the role of major international institutions—such as the World Health Organization (WHO), the United Nations (UN), and regional alliances—in navigating the pandemic. It discusses how fragmentation, underfunding, and geopolitical tensions limited the effectiveness of collective action, including vaccine distribution, supply chain coordination, and equitable access to resources. Despite these challenges, the crisis also prompted unprecedented levels of scientific cooperation and digital innovation, underscoring the potential for adaptive global collaboration. Drawing on these findings, the paper identifies key lessons for enhancing future global resilience. These include the need for stronger international legal frameworks, improved transparency and data-sharing protocols, sustainable financing of global health initiatives, and the reinforcement of multilateralism. Ultimately, the pandemic serves as both a warning and an opportunity, revealing the urgent need to reform global governance systems better to manage transnational crises in an increasingly interconnected world.